2015
DOI: 10.1002/adfm.201503493
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Small Molecules to Implement Organic Quaternary Memory Devices

Abstract: Organic small‐molecule‐based devices with multilevel electroresistive memory behaviors have attracted more and more attentions due to their super‐high data‐storage density. However, up to now, only ternary memory molecules have been reported, and ternary storage devices may not be compatible with the binary computing systems perfectly. In this work, a donor–acceptor structured molecule containing three electron acceptors is rationally designed and the field‐induced charge‐transfer processes can occur from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
93
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 115 publications
(95 citation statements)
references
References 57 publications
2
93
0
Order By: Relevance
“…After decades of intensive research, many inorganic oxides, 7 polymers 8 and small molecules 9,10 have been found to exhibit multilevel resistive switching behaviours and are thus considered candidate active materials for multilevel RRAMs. However, to enable industrial use, RRAM devices must show good reproducibility, including a high multilevel memory device yield and narrow distribution of OFF/ON1/ON2 switching voltages.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…After decades of intensive research, many inorganic oxides, 7 polymers 8 and small molecules 9,10 have been found to exhibit multilevel resistive switching behaviours and are thus considered candidate active materials for multilevel RRAMs. However, to enable industrial use, RRAM devices must show good reproducibility, including a high multilevel memory device yield and narrow distribution of OFF/ON1/ON2 switching voltages.…”
mentioning
confidence: 99%
“…Unfortunately, numerous studies have explored new RRAM active materials based on the measurements on individual devices, but statistical data on a large batch are rarely reported. 4 Our recent statistical work 9,1113 demonstrated that the ternary memory yield of organic RRAMs is generally low (∼50%), despite the effectiveness of the molecular design in improving the ternary yield and switching voltage distributions. The frustration of material innovation has urged us to seek other strategies for improving device reproducibility.…”
mentioning
confidence: 99%
“…The statistic result reveals that, the yield of ternary devices, as defined by the proportion of achieving output TROS behavior, is about 78 % (see from column‐chart plot in Figure d, left). Recent studies of TROS indicate that the ternary memory yields of some organic‐based materials are usually insufficient (≈50 %) . Regarding this defect, 1 could be considered as an excellent ternary NVM media with satisfactory reproducibility.…”
Section: Methodsmentioning
confidence: 97%
“…Meanwhile, the side view indicates that the ten‐ring molecular backbone is slightly curved (Figure e, bottom). Combined with the d ‐spacing obtained from XRD, the molecular aromatic cores are estimated to tilt approximately 55° with respect to the lamellar plane (sin θ = d ‐spacing/ M L ) . Figure f illustrates the probable molecular organization model of 1 , in which a tilt angle of 55° between the aromatic cores and lamellar plane is presented, along with the π–π plane separation of 3.47 Å.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation